2006
DOI: 10.1016/j.schres.2005.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Schizotypy is increased in mixed-handers, especially right-handed writers who use the left hand for primary actions

Abstract: Associations between schizotypy and handedness were examined in 733 undergraduates for the Sta and Unex scales of the O-Life inventory and several measures derived from the Annett hand preference questionnaire. Higher schizotypy scores were found for mixed-handers defined in various ways, including inconsistent preference for any item of the questionnaire and also the presence of either hand responses. There was a marked elevation of schizotypy scores (p < .001) for righthanded writers who prefer the left hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 23 publications
3
22
1
Order By: Relevance
“…Annett's 7-and 3-way classifications showed that lefthanders did not differ significantly from other groups. Contrary to previous findings Moran, 2006 andShaw et al, 2001), the pure left-handed group did not differ from the mixed-or right-handed groups. In our study, Annett's 7-way right-handers with strong/moderate left tendencies (i.e., mixed handed) were more psychosis-prone than pure right-handed subjects.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Annett's 7-and 3-way classifications showed that lefthanders did not differ significantly from other groups. Contrary to previous findings Moran, 2006 andShaw et al, 2001), the pure left-handed group did not differ from the mixed-or right-handed groups. In our study, Annett's 7-way right-handers with strong/moderate left tendencies (i.e., mixed handed) were more psychosis-prone than pure right-handed subjects.…”
Section: Discussioncontrasting
confidence: 99%
“…Some of our findings are consistent with previously reported studies on the association of handedness with psychosis-proneness in nonclinical samples (e.g., Somers et al, 2009, Chapman et al, 2011and Hori et al, 2012. Corroborating previous findings (Shaw et al, 2001, Gregory et al, 2003and Annett and Moran, 2006, writing hand alone was not associated with psychosis-proneness. Annett's 7-and 3-way classifications showed that lefthanders did not differ significantly from other groups.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations